Peran Pemerintah dalam Mendorong Pertumbuhan Ekonomi Syariah melalui Kebijakan Fiskal - Desfiansyah, Fadlan; Az-Zahra, Nabilla; Shifa, Maylaffayza Permata; Zahra, Fatimah (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Fiscal policy in encouraging Islamic economic growth is urgently needed to create new opportunities and increase the competitiveness of the Islamic economic sector. Broadly speaking, fiscal policy that is oriented towards sharia principles includes increasing welfare through maintaining faith, soul, mind, wealth and property. Islamic finance that operates according to Islamic principles with the aim of encouraging more investors to invest in this sector and increasing market liquidity. Fiscal policy in Indonesia is controlled through various instruments such as taxes, subsidies and government spending. The research method used in this article is literature review, which is a structured, detailed and iterative method for identifying, evaluating and synthesizing works produced by researchers and practitioners. Likewise, the form of implementing fiscal policy that has been implemented in supporting Islamic economic growth includes reducing taxes for Islamic companies, providing incentives for Islamic companies, and using zakat and waqf funds to support Islamic economic efforts.